Carbon‐Supported Copper Nanomaterials: Recyclable Catalysts for Huisgen [3+2] Cycloaddition Reactions. Issue 30 (18th June 2015) - Shaygan Nia, Ali; Rana, Sravendra; Döhler, Diana; Jirsa, Franz; Meister, Annette; Guadagno, Liberata; Koslowski, Eik; Bron, Michael; Binder, Wolfgang H.
Abstract Highly disperse copper nanoparticles immobilized on carbon nanomaterials (CNMs; graphene/carbon nanotubes) were prepared and used as a recyclable and reusable catalyst to achieve CuI‐catalyzed [3+2] cycloaddition click chemistry. Carbon nanomaterials with immobilized N‐heterocyclic carbene (NHC)‐Cu complexes prepared from an imidazolium‐based carbene and CuI show excellent stability including high efficiency at low catalyst loading. The catalytic performance evaluated in solution and in bulk shows that both types of Cu‐CNMs can function as an effective recyclable catalysts (more than 10 cycles) for click reactions without decomposition and the use of external additives.